Cours sur les Origines de la Vie Religieuse (1907) - Santos, Geovane Campanher dos (2024)
This project will aim to translate the essays published between 1887-1914 that address the theme of religious phenomena and their specific implications in the configuration of societies. This includes everything from their general foundations to their intrinsic correlation with the dynamics of morality (the ultimate condition for the modal determination of collective consciousnesses and, correspondingly, their solidarities). Accordingly, the first publication we will undertake will be the "Course on the Origins of Religious Life" (1907), in which Durkheim intends to establish the essential definitions of the concept of religion and its main structural attributes; that is, the intrinsic correlation between the sacred and the profane.